Study of mathematical models of type 2 diabetes mellitus and its complications - MAGHFIRAH, AFIATUN; GANI, BASRI A.; RAMLI, MARWAN; IKHWAN, MUHAMMAD (Jurnal Natural, 2024)
The rapid increase in type 2 diabetes mellitus (DM) cases in Indonesia, driven by hereditary factors and unhealthy lifestyles, poses significant health challenges. This study develops a compartmental model to analyze the progression of type 2 DM and the onset of complications, classifying individuals into susceptible, patients without complications, patients with complications, and those disabled due to complications. The model examines the influence of two key factors on the recovery from complications: habitual factors, including medication adherence, physical activity, dietary habits, smoking history, and environmental factors, such as stress levels, environmental support, patient trust, and compliance. The results indicate that habitual factors have a more substantial impact on mitigating complications compared to environmental factors, suggesting that lifestyle interventions are crucial in improving patient outcomes. The model also shows that an increase in behavioral interactions leading to disease progression results in instability, emphasizing the need for early and consistent behavioral interventions. This research offers valuable insights for healthcare providers and policymakers. By identifying the most influential factors in managing complications, the model can guide the development of targeted interventions that prioritize habitual changes, such as medication adherence and physical activity. Public health strategies can be tailored to emphasize the importance of these habitual factors, potentially reducing the burden of type 2 DM complications. Overall, this study highlights the critical role of personalized, behavior-focused interventions in the management and prevention of complications in patients with type 2 DM, offering a practical framework for improving patient care.